A remarkable new species of Eucyphonia Sakakibara, 1968 (Hemiptera: Membracidae): the hidden beauty of entomological collections - Rodríguez-Serrano, Juanita; Raupach, Michael J. (Zootaxa, 2026)
Eucyphonia Sakakibara, 1968, originally described as Cyphonia Laporte, 1832, is characterized by its elaborated pronotum, featuring bilobed suprahumeral processes and ornate posterior process. Examination of Membracidae material housed at the Natural History Museum of Vienna revealed a remarkable new species from Brazil, Eucyphonia nuggetta Rodríguez-Serrano & Raupach sp. nov. This species can be readily distinguished by its ochre body coloration with brown shading and a uniquely coarsely tuberculate pronotal surface, markedly differing from that of other Eucyphonia species. A detailed description and illustrations of this species are provided, together with an updated identification key for Eucyphonia. With this addition, the number of known species in the genus increases to ten. Our findings highlight the critical role of museum collections for documenting hidden diversity and refining taxonomic knowledge in poorly studied groups.